Nutritional, functional and sensory properties of gluten-free composite flour produced from plantain (Musa AAB), tigernut tubers (Cyperus esculentus) and defatted soybean cake (Glycine max) - Ijarotimi, Oluwole Steve (Array, 2019)
Plantain, tigernut and soycake were processed into flour and blended to obtain PSB (plantain, 64.46; soycake, 35.54%); TNS (tigernut, 59.83; soycake, 40.17%); PTS (plantain, 51.07; tigernut, 11.50; soycake, 37.43%); TNT (100% tigernuts); PLT (100% plantain), and CNT (a commercial flour) samples. The blended samples were evaluated for nutritional, antinutritive, functional and sensory attributes. Data were analysed using statistical package and means were subjected to ANOVA and separated using Duncan New Multiple Range (DNMR) test at p<0.05. Protein content (g/100 g) of experimental dough meals ranged from 16.22 to 29.72, and were significantly (p<0.05) higher than PLT (9.45) and CNT (14.29), while energy values (Kcal/100 g) ranged from 399.63 to 488.86. Phosphorus, iron, zinc and manganese concentration in experimental samples were significantly higher (p<0.05) than in PLT, but comparable to CNT. Total amino acids (mg/100 g protein) of experimental food samples ranged from 63.48 to 74.25, and were significantly (p<0.05) higher than CNT (60.91) and PLT (67.3). For saturated, monounsaturated and polyunsaturated fatty acid, the range values were 14.86-21.29, 55.14-56.56 and 23.14-27.84%, respectively. As far as polyunsaturated/saturatedn ratios are concerned, the values ranged from 1.09 to 1.92, and were higher than CNT (1.40).In conclusion, the study established that composite flour produced from plantain, tigernut and soycake were rich in essential amino acids and fatty acids, low in antinutritional factors and they exhibited good functional properties. Hence, the composite flour samples may be suitable for production of functional bakeries and dough products, particularly for diabetes and coeliac disease.